1998
DOI: 10.1074/jbc.273.3.1316
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Yeast Protein Deg1 as Pseudouridine Synthase (Pus3) Catalyzing the Formation of Ψ38 and Ψ39 in tRNA Anticodon Loop

Abstract: The enzymatic activity of yeast gene product Deg1 was identified using both disrupted yeast strain and cloned recombinant protein expressed in yeast and in Escherichia coli. The results show that the DEG1-disrupted yeast strain lacks synthase activity for the formation of pseudouridines ⌿ 38 and ⌿ 39 in tRNA whereas the other activities, specific for ⌿ formation at positions 13, 27, 28, 32, 34, 35, 36, and 55 in tRNA, remain unaffected. Also, the His 6 -tagged recombinant yeast Deg1p expressed in E. coli as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
162
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(168 citation statements)
references
References 45 publications
5
162
1
Order By: Relevance
“…Highly conserved homologues of Cbf5p share a high level of sequence similarity with known ⌿ synthases+ A: Amino acid alignment of the S. cerevisiae Cbf5p (accession no+ L12351), S. pombe Cbf5p (accession no+ Z97210), rat NAP57 (accession no+ Z34922), C. elegans (accession no+ Z92803), Drosophila (accession no+ AF017230), and Methanococcus (accession no+ U67472) Cbf5p/NAP57 protein homologues+ The sequences of the E. coli (accession no+ P09171) and Haemophilus influenza (accession no+ P45142) TRUB ⌿ synthases are also included as a comparison+ Identical residues are indicated in white on black boxes+ Conserved residues are indicated by grey boxes and are grouped as in Figure 5+ The boxed regions represent the two conserved regions found in the majority of ⌿ synthases+ Amino acid positions are indicated on the left+ Dashed lines indicate spaces inserted to align the amino acid sequences+ Only the homologous sequences have been included in this alignment+ B: Amino acid alignment of the highly charged C-terminal domains of Cbf5p homologues from S. cerevisiae, S. pombe, K. lactis (accession no+ AF008563), Dictyostelium discoidium (accession no+ C23692), rat, human (accession no+ U59151), Drosophila, and C. elegans+ KKE or KKD amino acid repeats are indicated in white on black boxes+ Other charged amino acids are indicated by grey boxes+ region of the snoRNA, and hence resemble the twodomain structure seen using the electron microscope (Fig+ 9)+ The extremely high degree of sequence identity seen between Cbf5p and other known ⌿ synthases suggests that this protein is indeed the enzyme activity responsible for snoRNA-directed modification (Koonin, 1996)+ While preparing this article, a paper describing Cbf5p as an integral H/ACA snoRNP protein involved in snoRNA biogenesis, 18S rRNA processing, and ⌿ synthesis was published (Lafontaine et al+, 1998)+ This suggests that the H/ACA snoRNPs are individual ⌿ synthases with the RNA component functioning in substrate recognition through direct base-pairing interactions+ The ⌿ synthases studied so far do not contain an RNA subunit and recognize the substrate through protein-RNA interactions (Kammen et al+, 1988;Nurse et al+, 1995;Wrzesinski et al+, 1995a,b;Simos et al+, 1996;Lecointe et al+, 1998)+ Hence, the H/ACA snoRNPs represent a novel type of modification enzyme+ In comparing the amino acid sequence of Cbf5p with known ⌿ synthases it is clear that the longer snoRNP protein contains essential highly conserved domains not present in the prokaryotic modification enzymes+ If one considers the fact that Cbf5p is essential for ribosome biogenesis and is proposed to interact with several other nucleolar proteins (Meier & Blobel, 1994;Cadwell et al+, 1997), this suggests that Cbf5p has other roles in the structure and function of this class of snoRNPs in addition to catalyzing ⌿ synthesis+ FIGURE 8. Electron microscopy of yeast snR30 and snR42 snoRNP complexes+ Purified snR30 and snR42 snoRNP complexes were negatively stained with uranyl formate+ Three common classes of (A) snR30 snoRNP and (B) snR42 snoRNP images+ For each row five examples of each class are shown of both the snR30 and snR42 complexes+ The corresponding rows in A and B show the respective particle in a similar projection form+ The left and mid...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly conserved homologues of Cbf5p share a high level of sequence similarity with known ⌿ synthases+ A: Amino acid alignment of the S. cerevisiae Cbf5p (accession no+ L12351), S. pombe Cbf5p (accession no+ Z97210), rat NAP57 (accession no+ Z34922), C. elegans (accession no+ Z92803), Drosophila (accession no+ AF017230), and Methanococcus (accession no+ U67472) Cbf5p/NAP57 protein homologues+ The sequences of the E. coli (accession no+ P09171) and Haemophilus influenza (accession no+ P45142) TRUB ⌿ synthases are also included as a comparison+ Identical residues are indicated in white on black boxes+ Conserved residues are indicated by grey boxes and are grouped as in Figure 5+ The boxed regions represent the two conserved regions found in the majority of ⌿ synthases+ Amino acid positions are indicated on the left+ Dashed lines indicate spaces inserted to align the amino acid sequences+ Only the homologous sequences have been included in this alignment+ B: Amino acid alignment of the highly charged C-terminal domains of Cbf5p homologues from S. cerevisiae, S. pombe, K. lactis (accession no+ AF008563), Dictyostelium discoidium (accession no+ C23692), rat, human (accession no+ U59151), Drosophila, and C. elegans+ KKE or KKD amino acid repeats are indicated in white on black boxes+ Other charged amino acids are indicated by grey boxes+ region of the snoRNA, and hence resemble the twodomain structure seen using the electron microscope (Fig+ 9)+ The extremely high degree of sequence identity seen between Cbf5p and other known ⌿ synthases suggests that this protein is indeed the enzyme activity responsible for snoRNA-directed modification (Koonin, 1996)+ While preparing this article, a paper describing Cbf5p as an integral H/ACA snoRNP protein involved in snoRNA biogenesis, 18S rRNA processing, and ⌿ synthesis was published (Lafontaine et al+, 1998)+ This suggests that the H/ACA snoRNPs are individual ⌿ synthases with the RNA component functioning in substrate recognition through direct base-pairing interactions+ The ⌿ synthases studied so far do not contain an RNA subunit and recognize the substrate through protein-RNA interactions (Kammen et al+, 1988;Nurse et al+, 1995;Wrzesinski et al+, 1995a,b;Simos et al+, 1996;Lecointe et al+, 1998)+ Hence, the H/ACA snoRNPs represent a novel type of modification enzyme+ In comparing the amino acid sequence of Cbf5p with known ⌿ synthases it is clear that the longer snoRNP protein contains essential highly conserved domains not present in the prokaryotic modification enzymes+ If one considers the fact that Cbf5p is essential for ribosome biogenesis and is proposed to interact with several other nucleolar proteins (Meier & Blobel, 1994;Cadwell et al+, 1997), this suggests that Cbf5p has other roles in the structure and function of this class of snoRNPs in addition to catalyzing ⌿ synthesis+ FIGURE 8. Electron microscopy of yeast snR30 and snR42 snoRNP complexes+ Purified snR30 and snR42 snoRNP complexes were negatively stained with uranyl formate+ Three common classes of (A) snR30 snoRNP and (B) snR42 snoRNP images+ For each row five examples of each class are shown of both the snR30 and snR42 complexes+ The corresponding rows in A and B show the respective particle in a similar projection form+ The left and mid...…”
Section: Discussionmentioning
confidence: 99%
“…The rRNA ⌿ synthase has yet to be identified; however, it is entirely possible that the protein responsible for the enzymatic activity is an integral component of the H/ACA snoRNPs+ The prokaryotic tRNA and rRNA ⌿ synthases do not use a guide RNA to recognize specific RNA substrates+ Multiple tRNA ⌿ synthases exist in prokaryotes that recognize either a single site or several sites with a similar structure (Kammen et al+, 1988;Nurse et al+, 1995;Wrzesinski et al+, 1995a,b;Simos et al+, 1996;Lecointe at al+, 1998)+ Therefore, the use of a guide RNA to direct rRNA ⌿ synthesis in eukaryotes is quite unique (Ganot et al+, 1997a;Ni et al+, 1997)+ It has recently been demonstrated that Gar1p, a protein common to all H/ACA snoRNPs, is required for ⌿ formation in yeast (Bousquet-Antonelli et al+, 1997)+ It is, however, highly unlikely that this protein is the modification enzyme, because Gar1p has little homology to known ⌿ synthases and is therefore postulated to function as an accessory protein in this event (Bousquet-Antonelli et al+, 1997)+ One possible candidate for the ⌿ synthase is Cbf5 (mammalian homologue NAP57; Meier & Blobel+, 1994), a nucleolar protein involved in ribosome biogenesis that shows a remarkably high degree of sequence similarity with known ⌿ synthases (Koonin, 1996;Cadwell et al+, 1997)+ Indeed, while we were preparing this article, a paper describing Cbf5p as an integral H/ACA snoRNP protein involved in snoRNA biogenesis, 18S rRNA processing, and ⌿ synthesis was published (Lafontaine et al+, 1998)…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an ;1,280-amino-acid-long N-terminal extension in Trm3p, as compared with spoU and other prokaryotic homologs, is intriguing+ In contrast, the four pseudouridine synthases that modify yeast tRNAs are only moderately longer than their E. coli homologs, truA and truB (Simos et al+, 1996;Becker et al+, 1997a;Lecointe et al+, 1998)+ Given that spoU and Trm3p appear to recognize the same three-dimensional architecture of mature tRNAs in E. coli or in yeast, the long N-terminal domain of Trm3p seems unlikely to be directly involved in the methylase catalytic activity or in substrate recognition+ The intracellular location of Trm3p remains unknown+ However, it is noteworthy that Pus1p, a tRNA pseudouridine synthase with an introndependent activity, is a nuclear protein interacting genetically with nuclear pore protein Nsp1p (Simos et al+, 1996)+ Likewise, splicing of tRNA may be coupled to tRNA export through the nuclear pore complex, given that the tRNA endonuclease appears to be an integral nuclear membrane protein (Peebles et al+, 1983) and that the tRNA ligase is localized close to nuclear pores (Clark & Abelson, 1987)+ Moreover, Trm1p that catalyzes formation of tRNA N2, N2-dimethylguanosine localizes at or near the nuclear membrane (Rose et al+, 1992(Rose et al+, , 1995+ Since formation of Gm18, like a few other tRNA modifications, occurs only after intron excision, an association of Trm3p with the transport machinery and/or the nuclear pore complex through its N-terminal domain may be envisioned+ Alternatively, Trm3p could reside in the cytoplasm and its long extension at the N-terminus could be required for its assembly into a macromolecular complex in much the same way as the aminoacyl-tRNA synthetase complexes in higher eukaryotes (Mirande, 1991;Kisselev & Wolfson, 1994)+…”
Section: Peculiarities Of the Putative Eukaryotic Enzymementioning
confidence: 99%
“…Formation of a given type of nucleotide modification at multiple sites of an RNA molecule frequently involves several distinct modifying activities, but some enzymes can modify different positions within an RNA substrate (Simos et al+, 1996;Lecointe et al+, 1998), and a dual substrate specificity can even be envisioned (Wrzesinski et al+, 1995)+ Analysis of TRM3-disrupted yeast strain tRNAs and in vitro modification experiments of tRNA transcripts indicate that Trm3p has a very narrow substrate and site specificity, corresponding to the exclusive formation of Gm18 in all yeast cytoplasmic tRNAs naturally bearing this methylation+ Several instances of a single nuclear gene encoding an enzyme modifying both cytoplasmic and mitochondrial tRNAs have been reported (Hopper et al+, 1982;Becker et al+, 1997a;Lecointe et al+, 1998), and the possibility that Trm3p is also responsible for Gm18 formation in mitochondrial tRNAs cannot be ruled out+ In E. coli RNA, a total of seven 29-O-ribose-methylated nucleotides have been identified, including two other tRNA ribose methylations in addition to Gm18, Um32, and Cm32, the formation of which might be catalyzed by the same enzyme different from spoU+ As for the four rRNA ribose methylations, one of which is on a guanosine (Smith et al+, 1992), they do not depend upon spoU but are thought to each involve a distinct methylase (Gustafsson et al+, 1996)+ Accordingly, we have detected 6 ORFs encoding putative RNA ribose methylases in the E. coli genome (Table 1)+ While a pseudouridine synthase capable of forming c32 in tRNA Phe in vitro also catalyzes specific formation of c746 in E. coli 23S rRNA (Wrzesinski et al+, 1995), our data do not provide evidence for a dual substrate specificity of Trm3p+ Since sites of cytoplasmic rRNA ribose methylations are exclusively specified by the RNA duplex structure involving a cognate small nucleolar RNA guide (Cavaillé et al+, 1996;Kiss-Laszlo et al+, 1996;Nicoloso et al+, 1996;Bachellerie & Cavaillé, 1997) the involvement of only a few, if not a single rRNA ribose methylase, devoid of any site specificity and obviously distinct from Trm3p, seems likely+ As for snRNAs, which contain phylogenetically conserved ribose-methylated nucleotides (including several guanosines) in vertebrates, their ribose methylation patterns in S. cerevisiae are not known (Massenet et al+, 1998)+ However, given that Trm3p activity is strongly dependent in vitro on the three-dimensional conformation of mature tRNA, as discussed below, its involvement in snRNA ribose methylation seems unlikely+ Finally, yeast mRNAs are devoid of ribose methylations adjacent to the 59 cap, in contrast to vertebrate mRNAs (Narayan & Rottman, 1992)+…”
Section: Substrate and Site Specificity Of Trm3pmentioning
confidence: 99%
See 1 more Smart Citation